2018
DOI: 10.1136/vr.104492
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D shows in vivo efficacy in a placebo‐controlled, double‐blinded, randomised clinical trial on canine atopic dermatitis

Abstract: Atopic dermatitis (AD) in dogs is among the most common skin diseases in small animal practice. It is an inflammatory disease based on a genetic predisposition to develop hypersensitivity against environmental and food allergens and typical clinical signs up exposure. Treatment sometimes can be difficult and associated with adverse effects. Previous studies evaluating cholecalciferol as treatment for human AD have shown promising results. With canine AD being a good animal model for its human counterpart, it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 61 publications
(106 reference statements)
0
27
0
Order By: Relevance
“…Vitamins D supplementation has shown to be beneficial in case of AD [95] while vitamin E acts as an antioxidant improving the clinical status of dogs with moderate AD [96][97][98], reducing the biosynthesis of prostaglandin E2 [99], inhibiting formation of IgE and decreasing its amount [100,101].…”
Section: Vitamins and Mineralsmentioning
confidence: 99%
“…Vitamins D supplementation has shown to be beneficial in case of AD [95] while vitamin E acts as an antioxidant improving the clinical status of dogs with moderate AD [96][97][98], reducing the biosynthesis of prostaglandin E2 [99], inhibiting formation of IgE and decreasing its amount [100,101].…”
Section: Vitamins and Mineralsmentioning
confidence: 99%
“…15 Antimicrobial peptides (AMPs) also play an important role in skin barrier function through innate immunity in human and canine atopic dermatitis, 16 so vitamin D might contribute to prevention of recurrent pyoderma, one of the regular phenomenon in canine atopic dermatitis. 17 The aim of the Klinger study 8 is in agreement with recently suggested clinical trials of canine atopic dermatitis that focus on the development of drugs able to restore the skin barrier and increase natural defences against pathogenic organisms. 18 The study was designed as a three-arm randomised, doubleblinded, placebo-controlled, cross-over trial.…”
mentioning
confidence: 68%
“…Based on the association between vitamin D and inflammation in human medicine, a correlation between circulating concentrations of 25(OH)D and the severity of atopic dermatitis signs in children has been demonstrated (Peroni, Piacentini, Cametti, Chinellato, & Boner, 2011). In veterinary medicine, a recent study investigated the effects of systemic administration of cholecalciferol in dogs with atopic dermatitis (Klinger et al, 2018). In this study, it was observed that dogs in the treatment group had lower lesion and pruritus scores when compared to those of the placebo group.…”
Section: Other Public Ationsmentioning
confidence: 95%